The Effect of Profitability, Leverage, and Company Size on Company Value: Empirical Study on Manufacturing Companies in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange - Kristom Eko Kanika; Rachmat Arief (Economics and Digital Business Journal, 2025)
This study aims to examine and analyze the effect of profitability, leverage, and firm size on firm value in the food and beverage manufacturing sub-sector companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sample was selected using a purposive sampling technique, resulting in 47 food and beverage companies listed on the Indonesia Stock Exchange during the 2021-2024 period. The data analysis technique employed was multiple linear regression analysis using SPSS software. The results indicate that, partially, profitability has a positive and significant effect on firm value, suggesting that profit-earning efficiency serves as a positive signal for investors. Conversely, leverage and firm size do not have a significant effect on firm value. Simultaneously, all three variables profitability, leverage, and firm size significantly influence firm value.